JAS ÁWLAD SANASÍNA RUWXÍY HÁM KÓRKEM ESTETIKANÍŃ JETISKENLIKLERIN SIŃDIRIW JOLLARÍ - Abdimuratov, P.S.; Seytanov, B.T. (SCIENCE and SOCIETY, 2024)
The article deals with the aetuentic emotions of a person and mechanisms of withstanding its effects.